Emotional Intelligence of Employee Excellence - A Study of Automobile Industry - Rani, Devika; Kalburgi, M. Javed; Begum, Mohammed Farzana (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
The primary goal of the paper is to explore the connection between emotional intelligence and employees’ satisfaction in India’s automobile Industry. The research examines the emotional intelligence variables and how employees’ control & understand the emotions of themselves and their colleagues. The study was conducted by taking 120 respondents selected randomly from automobile industry. The study prophecies the emotional quotient of employees in different aspects like self-awareness, self-regulation, motivation, empathy and social skills.